Florística e efeito de borda em fragmentos da floresta ombrófila mista na região de Guarapuava, PR - Silva, Adriana Massaê Kataoka (Universidade Federal de São Carlos, 2006)
This survey was carried out in a Araucaria Forest of an area of a legal reserve of Três Capões Farm and Trindade Farm, situated at south central of the state of Paraná, Brazil. The local climate is the tipe Cfb, don't have a dry season the average temperature is about 18oC at the more cold month. The average altitude is about 1250m cliff of scarp at 350m at Guarapuava region. The geomorfology is characterized by conver rill and largue valley originated on Quaternary. The forest in this study was sampled with transects positionaded at north, west, south and east, where the floristic surveyed was realized beyond the walk for all the area. A number of 144 species. The families with the highest number of species was Lauraceae (8,0%), Myrtaceae (8,0%), Solanaceae (7,2%), Euphorbiaceae (4,8%), Fabaceae (4,8%) and Verbenaceae (4,8%). Currently, forests are found as fragments inserted in a variety of matrixes. Hence, these fragments are under constant influence of the matrixes, fact known as edge effects. This work investigated the occurrence of edge effectsin the regulation of three Araucaria Forest fragments located in the south-center region of the Parana state, Brazil. Several approaches were realized in 12 transects of 4x100 m: floristic survey, density calculations, basal area, pioneer and secondary species, richness and behavior. A total of 3271 arborescent and arboreal specimens belonging to 152 species were sampled in the north, south, east and west side of the three forest fragments. There were no analyzed parameters that resulted in an expected pattern of edge effects. An ANOVA test was applied to analyze a correlation of the data with positioning (north, south, east and west) in each fragment. No significant correlation was detected in the fragments. The results are possibly related to the fact these fragments are not only under the edge effect, but also to the continous anthropic interference that could mask the known edge effects through the intensification of such interference farther than the first meters from the border to the interior of the fragment. This lead to another concern about this type of fragment because it could means a pure conservation of this vegetation, considering the small portion of conserved areas and discounted the edge effects.
Keywords: Ecologia de comunidades; Comunidades vegetais; Florística; Efeito de borda; Fragmentos florestais; Floresta ombrófila mista; CIENCIAS BIOLOGICAS::ECOLOGIA